A Socio Pragmatics Analysis Of Criticism Utterances In Romance Manuscripts - Istiqomah, Dyaswari (2007)
This research is aimed at finding the speaker's intentions, the reasons, and the politeness systems of criticism utterances. The data are criticism utterances in the form of words, phrases, and sentences that are taken from romance movie manuscripts; they are Te n Things I Hate about You, Runaway Bride, and Pretty Woman. In collecting the data, the writer uses document and observation method by applying techniques of reading the scripts, watching the movie, and then selecting the data which belong to criticism utterances. To describe the speaker's intention, the writer uses Speech Act theory especially locution, illocution, and perlocution. In clarifying the reasons, the writer uses SPEAKING theory by Dell Hymes. To describe the politeness system used in criticism utterances, the writer uses Politeness Strategy by Brown and Levinson. Having analyzed the data, the writer finds that there are nine intentions of criticism utterances. The intentions are to contradict, to advice, to mock, to order, to judge, to forbid, to satire, to remain and treat, and to blame. There are six reasons of criticism utterances; they are to show power, to show anger, to show disappointment, to show intimacy, to show solidarity, and to show astonishment. There are three politeness systems uses; they are bald on-record strategy, politeness strategy, and negative politeness.